(untitled) - Charlesworth, James H.; (1940-...) (U.S.A, 2006)
Based on studies at Bethsaida, Capernaum, Nazareth, Jerusalem, and elsewhere, this volume shows how recent archaeological studies clarify the world, life, and thought of Jesus of Nazareth. It contains the revised and edited lectures that leading archaeologists and biblical scholars presented at a gathering in Jerusalem to celebrate the new millennium. Many contributors came directly from their excavations in places like Bethsaida, Capernaum, Nazareth, and Jerusalem to share their discoveries and insights, focusing on the question In what ways do new archaeological discoveries clarify the world, life, and thought of Jesus from Nazareth? Readers of Jesus and Archaeology will gain many new insights into the life and times of this fascinating Galilean Jew.
Keywords: Bible -- New Testament -- Antiquities